Regional knowledge, entrepreneurial culture and innovative start-ups over time and space: An empirical investigation - Michael Fritsch; Michael Wyrwich (Friedrich Schiller University Jena, 2018)
We investigate the role of entrepreneurship culture and the historical knowledge base of a region on current levels of new business formation in innovative industries. The analysis is for German regions and covers the time period 1907-2014. We find a pronounced positive relationship between high levels of historical self-employment in science-based industries and new business formation in innovative industries today. This long-term legacy effect of entrepreneurial tradition indicates the prevalence of a regional culture of entrepreneurship. Moreover, local presence and geographic proximity to a technical university founded before the year 1900 is positively related to the level of innovative start-ups more than a century later. The results show that a considerable part of the knowledge that constitutes an important source of entrepreneurial opportunities is deeply rooted in history. We draw conclusions for policy and for further research.
Keywords: L26; L60; L80; O18; R12; R30; 330; Innovative start-ups; universities; regional knowledge; regional cultures of entrepreneurship